Influência do processamento por deformação plástica severa no comportamento mecânico, eletroquímico e citotóxico do magnésio - Claudio Laudares Passos Silva (2018)
Among the materials with potential for applications as biomaterials magnesium has received special attention due to their good combination of desirable (mechanical, biological and electrochemical) properties. Recent studies show that the processing of magnesium by severe plastic deformation refines the microstructure and improves the mechanical properties. The present work shows the microstructural and mechanical characterization of pure magnesium and commercial alloys AZ31, AZ91 and ZK60 after processing by ECAP (Equal-Channel Angular Pressing) and HPT (High Pressure Torsion). Commercially pure magnesium (CP-Mg) was processed by ECAP at high temperature and by HPT at room temperature. The magnesium alloys were processed by HPT at room temperature. To evaluate possible modifications in the mechanical properties caused by the processing tensile tests were performed at room temperature on magnesium samples and hardness distribution maps of HPT discs cross section were constructed. The corrosion rate of all samples was determined by electrochemical polarization tests and hydrogen evolution tests. The polarization resistance was also measured using electrochemical impedance spectroscopy (EIS) techniques. To compare the morphological aspects of the corrosive process in each sample, visual inspection tests with photographic record were also carried out. To evaluate the cytotoxicity, two different tests were used the MTT and the Live / Dead assays. The distribution and the average grain size in the samples at each processing stage were evaluated using metallography procedures and the image acquisition was performed by optical microscopy, scanning electron microscopy (SEM) and transmission electron microscopy (MET) in the case of samples with ultrafine microstructure. The results show that HPT processing refines the grain structure of magnesium and its alloys to submicron scale and significantly increases hardness. Biocompatibility is not affected by processing and the corrosion behavior varies depending on material. Grain refinement promotes a change from localized corrosion to generalized corrosion in pure magnesium. The electrochemical tests results do not show significant changes on corrosion behavior of magnesium alloys after processing by HPT.